PERS SEBAGAI MEDIA PERJUANGAN KEMERDEKAAN DALAM FILM BUYA HAMKA VOL 1 - Alpiodita, Yurin; Sukmawati, Lilis (NOUMENA: Jurnal Sosial Humaniora dan Keagamaan, 2024)
Journalists or reporters have a very important role in society.  With the press, various kinds of information can be disseminated for the sake of public knowledge about an important event or just information that is obtained.  This research is entitled "The Press as a Media for the Struggle for Independence in the Film Buya Hamka".  The research focuses on observing scans of the film Buya Hamka which are related to the press.  The role of journalists is to be a source of liaison between information and the public in order to get the latest news as quickly and accurately as possible.  Usually information can be obtained through word of mouth, print media such as newspapers and magazines, books and many other information media that surround us, the media is one of the nation's important institutions.  The research method used is a qualitative method with Roland Barthes' semiotic approach (denotation, connotation and myth).  The results of this research on this film show that there is a scane of a journalist's struggle to voice the press, so the importance of the press in this film is because this film highlights the press for the struggle for independence.  The research focuses on the press in the struggle for independence in Indonesia after conducting research observations seeing that this film has never been researched regarding the press, and the role of Buya Hamka in voicing the press through the media to fight for Indonesian independence.  The conclusion of the analysis in this film is related to the press as a medium for the struggle for independence.  Having an important role in independence, print media such as newspapers and magazines are a way of giving voice to the press, so that many Indonesian people can easily get it. Because newspapers and magazines are sources of existing news information, newspapers or magazines are sold at affordable prices, so that the press can reach all  circles from the lace class to the top.